Penempatan Access Point Pada Jaringan Wi-Fi di Sekolah Tinggi Teknologi Indonesia Tanjungpinang - Sugeng Riyanto; Rahmat Rahmat; Zulfachmi Zulfachmi (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2021)
In this research is done to know balance the position of Access Point on Wi-Fi network in Sekolah Tinggi Teknologi Indonesia Tanjungpinang campus. The power of existing Wi-Fi network is not optimal in serving the entire area, so it needs to balance Access Point to get best signal quality. Network performance analysis is done by measuring the signal strength and coverage area of access point using netspot software, inSSIDer and Wireless Wizard. The netspot software is used to determine the coverage area of the access point, while the inSSIDer and Wireless Wizard software is used for wireless signal monitoring and positioning of access points for the best signal reception in the research area. From the measurement results, calculations and analysis obtained, the number of access points needed to cover an area is determined by the type of access point used. When viewed from the access point identified in the measurement area of the placement position of the access point, distance is not the only determinant of the best signal received by the user, the construction of the building made of the wall and the obstacle factors also affect the signal quality of the access point used.